The compliance of contractor on providing the occupational safety system at the construction site (case study - government projects) / Zakaria Yaa’cob, Mohamad Sohaimi Man and Md. Yusof Hamid - Yaa’cob, Zakaria; Man, Mohamad Sohaimi; Hamid, Md. Yusof (2012)
Of late, we have seen many accidents take place, in controlled situation at the construction site. The contract has clearly stated the need of safety at construction site, unfortunately the contractor did not take serious action on it. All parties involved in the project must play their roles in resolving the problems. This phenomenon must be studied based on law and regulation such as Occupational Safety and Health Act 1974 and Machinery and Industry Act 1967 and the safety management system provided by the contractor. There are two methodologies are used in this research; one is based on the literature review in safety management system, such as safety policies, safety plan, accident reporting system, training, monitoring and supervising and risk assessment, legislation. The second methodology is to do a case study on government projects via conducting with the interviews to the target groups that are the contractors, members of professional, and safety officers. The analysis based on the finding of case studies for every item discuss and the result of the analysis will show that the level of compliance of contractor on providing the safety management system. At the end of this research, a proposal to contractor and government agencies for an improvement of management system at construction site such as to propose the percentage of cost on safety by cost of project, will be submitted